2018
DOI: 10.1002/pits.22192
|View full text |Cite
|
Sign up to set email alerts
|

Early elementary teacher ratings of behavior as predictors of grade retention: Race, gender, and socioeconomic status as potential moderators

Abstract: Our goals in this study were to examine (a) the degree to which teacher perceptions of children’s behavior in kindergarten (averaged across fall and spring for each child) predict retention by Grade 5 and (b) whether these relationships are moderated by student race, gender, or socioeconomic status (SES). Data from the Early Childhood Longitudinal Study, Kindergarten Class of 1998‐99 (ECLS‐K) were used to examine how Externalizing Problem Behavior (EPB; e.g., aggression, defiance) and Weak Approaches To Learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In this regard, more emotionally related interventions teaching the student a better growth mindset about their own skills may benefit their emotional results [ 92 , 93 , 94 ]. In addition, because many problems begin in kindergarten [ 95 ], more preventative approaches should be considered, such as the pre-kindergarten program, which offers a child-centered curriculum with strong literacy and language development while working hand-in-hand with parents [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, more emotionally related interventions teaching the student a better growth mindset about their own skills may benefit their emotional results [ 92 , 93 , 94 ]. In addition, because many problems begin in kindergarten [ 95 ], more preventative approaches should be considered, such as the pre-kindergarten program, which offers a child-centered curriculum with strong literacy and language development while working hand-in-hand with parents [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…When children display enhanced social–emotional skills in the classroom as a result of SEL intervention, it is possible that these enhanced competencies will reduce the likelihood that they will be retained in grade due to behavioral issues. Indeed, recent work by Mattison et al (2018) has found that kindergarten students whose teachers rate them to be high on externalizing behavior problems are more likely to be retained between first and fifth grades. Some quasi-experimental work has found that participation in SEL programs can reduce the probability that students will be retained in grade.…”
Section: Grade Retentionmentioning
confidence: 99%
“…Students' observable characteristics ( X ij ) include sex and socio-economic status. 16 These variables have previously been found to explain grade retention, with girls less likely to repeat than boys (Tingle et al, 2012) and lower socioeconomic status students more likely to repeat than their high socio-economic peers (Mattison et al, 2018). Other studies have analysed both gender and socioeconomic status simultaneously, finding similar results (García-Pérez et al, 2014;González-Betancor & López-Puig, 2016;Klapproth & Schaltz, 2015;Pedraja-Chaparro et al, 2015).…”
Section: Regression Discontinuity Modelmentioning
confidence: 88%
“…More than anything, evidence-based policy reforms to grade retention in Spain are needed, ranging from remedial education (Jimerson, 2001) to the previously described early childhood interventions (García-Pérez et al, 2014;Ou & Reynolds, 2010). Screening and diagnosing the potential learning difficulties of students as early as possible may also help avoid grade retention and its negative influences (González-Betancor & López-Puig, 2016;Mattison et al, 2018). Others have suggested that summer school programmes and academic and behavioural support may also be beneficial (Bowman, 2005;Jimerson & Ferguson, 2007;Mattison et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation